Flight of the Conchords. The complete first season [videorecording (DVD)] - Clement, Jemaine; Clement, Jemaine; Clement, Jemaine; McKenzie, Bret; McKenzie, Bret; McKenzie, Bret; Bobin, James; Bobin, James (HBO Video, 2007)
Two New Zealander friends experience life, love, friendship, all the usual stuff, while trying to make their lives as a rock band. Unfortunately, they're a rock band that can only schedule a performance at the local aquarium, and they have only one fan.